Between look and meaning: the role of images in identity and memory formation (Revista de Ensino em Artes, Moda e Design, 2025)
This article investigates the role of images in the construction of collective identities and memories from a philosophical perspective. Images, from cave art to the digital age, act as fundamental elements in the organization and preservation of social experiences, influencing historical narratives and structuring shared memories. The discussion is based on concepts from authors such as Maurice Halbwachs, Walter Benjamin and Roland Barthes, who explore the relationship between memory, identity and visual representation. In addition, the impact of the technical reproducibility of images and their political role in contemporary times is examined. The analysis seeks to demonstrate how visual culture shapes social consciousness, reinforcing or challenging dominant discourses.
Keywords: collective memory; cultural identity; visual representation; philosophy of the image; technical reproducibility